Role Of Metal Supported Catalysts And Their Characterization In The Catalytic Decomposition Of Methane For The Formation Of Uniform Carbon Nanotubes In A Single Step Process[T174.7. C434 2008 f rb]. - Chai, Siang Piao (2008)

(untitled)
Nanotiub karbon (CNTs) menarik perhatian para saintis di seluruh dunia kerana dimensi, kekuatan dan sifat-sifat fizikal yang istimewa membuatkannya satu bahan yang unik dengan banyak aplikasi. Carbon nanotubes (CNTs) have attracted the fancy of many scientists worldwide due to their small dimensions, strength and remarkable properties that make them a very unique material of a whole range of promising applications.